Four new stink bug mitogenomes corroborate the internal inconsistencies in the classification of Pentatomidae (Hemiptera) - Gonçalves, Leonardo Tresoldi; Pezzi, Pedro Henrique; Bianchi, Filipe Michels (Zootaxa, 2022)
Stink bugs (Pentatomidae) are a speciose group of insects that feed mostly on plants. Many species are considered agricultural pests of economically important crops around the globe. Mitochondrial genomes are valuable for evolutionary and phylogenetic studies, but have been little explored for Pentatomidae. Here, we characterized the mitochondrial genomes of four pentatomid species (Diceraeus melacanthus, Euschistus heros, Piezodorus guildinii, and Stiretrus anchorago) and performed a comparative analysis for this family and its subfamilies. Stink bug mitogenomes disclosed a conserved gene order and content, although we detected two uncommon armless tRNAs in E. heros and D. melacanthus. Phylogenetic results indicate that Pentatominae is polyphyletic, showing that internal relationships of Pentatomidae should be further investigated. Stink bug mitochondrial genes are under strong purifying selection, except for ATP8 which showed signs of positive selection.